2018
DOI: 10.1088/1741-2552/aac313
|View full text |Cite
|
Sign up to set email alerts
|

Multiband tangent space mapping and feature selection for classification of EEG during motor imagery

Abstract: The increased classification accuracy of MI tasks with the proposed MTSMS approach can yield effective implementation of BCI. The mutual information-based subband selection method is implemented to tune operation frequency bands to represent actual motor imagery tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 63 publications
0
29
1
Order By: Relevance
“…Zhang et al used OVR-FBCSP combined with CNN+LSTM method for MI recognition [53]. Islam et al used TSM to find the precise frequency band associated with the MI mission for MI recognition [41]. In their work, the optimal MI recognition accuracy based on the sub-band selection method of mutual information is 82.6%±13.06, which is lower than our experimental result 90.09% and proves that the effect of FBCSP is feasible for MI recognition.…”
Section: B Different Frequency Range Selectioncontrasting
confidence: 64%
“…Zhang et al used OVR-FBCSP combined with CNN+LSTM method for MI recognition [53]. Islam et al used TSM to find the precise frequency band associated with the MI mission for MI recognition [41]. In their work, the optimal MI recognition accuracy based on the sub-band selection method of mutual information is 82.6%±13.06, which is lower than our experimental result 90.09% and proves that the effect of FBCSP is feasible for MI recognition.…”
Section: B Different Frequency Range Selectioncontrasting
confidence: 64%
“…Let us consider that one has a set of matrices P which have m × m dimensions. As represented in [17], this set can be defined as P(m)={PnormalS(m)|uTPu>0, normalu Rm, u0}, where S(m) indicates the space of all symmetric matrices. Moreover, this creates a manifold with the dimension m(normalm+1)/2.…”
Section: Related Studiesmentioning
confidence: 99%
“…However, the problem is very challenging due to very different locations of electrodes and subjects-specific nature of epilepsy events. In addition, Islam et al 26 reported that the appropriate selection of operational subbands can significantly improve the system performance due to subject-specific nature of EEG signals. Therefore, the possible extension of this study is to detect the most significant subbands in the high-frequency components, which may further improve our system performance in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a filter bank, which is an array of bandpass filters, was applied to decompose an EEG signal into a set of analysis signals exhibiting multiple subband frequency components 64,65 . To develop more accurate detection of brain activities related to the specific mental tasks, EEG-based studies proposed the filter-bank method to divide the wide frequency ranges into narrow subbands [24][25][26] . More specific, Higashi et al proposed a filter-bank approach to improve the performance of MI-BCI, which decomposed the 4-40 Hz frequency ranges into 6 subbands with a bandwidth of 6 Hz each 66 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation